Parameters of sagittal alignment of lumbar spine - Shrestha, Prabin; Shidoh, Satoka; Lee, Jangbo; Yamaguchi, Satoshi (Nepal Journal of Neuroscience, 2025)
Sagittal alignment of lumbar spine (SALS) is the state of spine in sagittal plane. The spine is a single organ with multiple segments of varying structure and function. These segments are interrelated and can be the cause and effect of malfunction of the other. In addition, there is a significant role of pelvis and cranium in maintaining the global sagittal balance. The lumbar spine plays a vital role in maintaining global sagittal balance because of several factors. Lumbar lordosis (LL) is one of them which helps to distribute body weight evenly to maintain an upright position. In other words, by virtue of LL, human beings can stand upright and walk with perfect balance. LL is basically a compensatory posture and any change in it beyond the normal limit needs further compensation by other parts of the spine and pelvis in order to restore balance. This compensation occurs at the cost of excessive stress in those other parts. Ultimately it can affect overall spinal alignment leading to loss of sagittal balance which in turn results in series of clinical manifestations like chronic back pain and difficulty in walking, bending and standing. There are various parameters which help to define a perfect SALS. Spinal surgeons should have a good understanding of these parameters not only for the proper evaluation of any spinal problem but also for the appropriate planning of spinal surgery.